RME BERBANTUAN GAME EDUKASI KAHOT: PENGARUHNYA TERHADAP KEAKTIFAN dan HASIL BELAJAR SISWA pada MATERI FUNGSI KOMPOSISI - Kusnandar, Ari; Sutarto; Kurniawan, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student engagement and mathematics learning achievement, particularly in composite function material, represent a persistent challenge requiring innovative pedagogical solutions. This study empirically investigates the effect of the Realistic Mathematics Education (RME) model integrated with the Kahoot gamification platform on the activeness and learning outcomes of eleventh-grade students at SMA Negeri 4 Mataram. A quasi-experimental design with a pretest-posttest non-equivalent control group structure was employed. Cluster random sampling was applied to select class XI IS 1 as the experimental group and XI IS 2 as the control group, each comprising 31 students. Student activeness was measured using a Likert-scale observation sheet, while learning outcomes were assessed through essay-based instruments administered at pretest and posttest stages. Data were analyzed using the Independent Samples T-Test and N-Gain Score calculations in SPSS at a significance level of α = 0.05. Findings revealed that the experimental group achieved a mean activeness score of 59.26 against 41.19 in the control group, yielding t = 12.676 with significance < 0.001. For learning outcomes, the experimental group's posttest mean reached 82.42 compared to the control group's 66.61, with t = 5.840 and significance < 0.001. N-Gain Score analysis further confirmed these differences, placing the experimental group in the medium category (0.41) and the control group in the low category (0.23). These results establish that the RME model assisted by Kahoot exerts a significant positive influence on both student activeness and mathematics learning outcomes in composite function material.